Needs analysis-based design principles for constructing a context-aware English learning system. Issue 1 (2nd January 2023) - Chiu, Wan-Yu; Liu, Gi-Zen; Barrett, Neil E.; Liaw, Meei-Ling; Hwang, Gwo-Jen; Lin, Chih-Chung
Abstract: In response to the needs of an international workforce, English for Specific Purpose courses are being promoted in higher education, and instructors are turning to learning technology to help design the instruction. In this paper, a needs analysis was conducted to guide the design of the system, materials and activities for context-aware ubiquitous language learning (CAULL) and English for Fitness Purposes (EFP) in a fitness center as part of a Design-Based Research project. The data collection methods included on-site observations, semi-structured interviews, and a questionnaire. The participants included 82 undergraduate students, seven physical education (PE) instructors, and six non-PE faculty members who frequently used the fitness center. All data forms were then triangulated and analyzed. The results show that all three groups consistently agreed that they need receptive language skills as well as specific terminology for fitness. Furthermore, it was suggested that the oral communication skills for EFP learners should also be developed for sharing ideas, experience, and suggestions. They pointed out that vocabulary related to diverse topics such as warm-up and cool-down stretches, cardiovascular exercises, and weight training are needed. Furthermore, participants reported that the CAULL system should be hypermedia-based, and contain a portfolio and a user-friendly interface. The findings were used to develop a blue print for a CAULL system based on design principles. The findings are of interest to context-aware language learning researchers, instructional designers, and the field of English for Specific Purposes.